Effect of Policy and Employee Capacity on the Provision of Quality Service among Private Security Firms for Mitigating Crime in Nairobi County in Kenya - Ekwenye, Otte Zebedee (2021)
This study assessed effect of policy and employee capacity on the provision of quality service among private security firms for mitigating crime in Nairobi County in Kenya. The specific objectives were to explore how policy and employee capacity affect the provision of quality service among PSFs for mitigating crime in Nairobi County in Kenya. The study was guided by SERVQUAL theory. This study used descriptive survey design with structured questionnaires as the instrument for data collection. The study targeted top managers, assistant managers and the immediate supervisors in 55 Private security firms registered under KISIA in Nairobi County. A census was used to sample the respondents of the study. The study employed drop and pick method to administer the questionnaires to the respondents. The study also conducted a pilot study on 10 respondents’ to check for the reliability and validity of the research instrument. The respondents who partook in the pilot study were no included in the final study. The data was analyzed using SPSS version 21 to achieve the study results. Descriptive statistics was presented using; pie charts, frequency table, and graphs. Correlation and regression analysis results were presented using tables. Results of the study revealed that policy and employee capacity has a positive and significant influence on the provision of quality service for mitigating crime among the private security firms in in Nairobi County. The study established that the adoption of the right policies such as compliance with the KISIA regulations has a positive influence on the provision of quality security service by PSFS for mitigating crime in Nairobi County. The study also established that employee capacity positively and significantly influences the provision of quality security service for mitigating crime among PSFs in Nairobi County. The study recommends the Public Security Firms to ensure they comply with KISA regulations to allow for effective provision of standard quality of security. The study recommends the PSFs to put in place proper control structures to assess the suitability of their staff. PSFs should also adopt proper training methods with the current technical skills and knowledge, and interactive skills. Key Terms: Policy, Employee Capacity, Quality Service, Crime Mitigation, Private Security Firms DOI: 10.7176/PPAR/11-6-03 Publication date:July 31st 202